Experimental Study of Effective Parameters in Production of Carbamazepine Nanoparticles - Fariba Shadmobaraki; Seyed Siamak Ashraf Talesh (Iranian Journal of Chemistry & Chemical Engineering, 2015)
In this study, confined impinging liquid jets are used to produce nanoparticles of carbamazepine (CBZ). The effect of operating parameters, such as the kind of solvent,CBZ concentration, flow rate of solution and antisolvent on particle size, are experimentally investigated. The Scanning Electron Micrograph (SEM) photomicrographs show that nanodrug with smaller particle is achievable by using solvent with more supersaturation. Meanwhile, decreasing concentration causes the production of smaller particles in the range of 430 to 190nm and by increasing flow rate of solution, the particle size increases from 240 to 340 nm. Furthermore, the physical states of particles are investigated by Differential Scanning Calorimetry (DSC) test.